2020
DOI: 10.1038/s41598-020-64055-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Kidney Donor Profile Index Scores on Post-Transplant Clinical Outcomes Between Elderly and Young Recipients, A Multicenter Cohort Study

Abstract: We investigated if clinical outcomes after kidney transplantation (KT) from deceased donors (DDs) with high Kidney Donor Profile Index (KDPI) can be different according to the age of KT recipients (KTRs). Six-hundred fifty-seven KTRs from 526 DDs were included from four transplant centers. We divided KTRs into elderly-KTR and young-KTR groups based on age 60 and each group was subdivided into high-or low-KDPI subgroup based on KDPI score of 65%. We compared short-term and long-term clinical outcomes among thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…6,7 Current allocation policies attempt to match recipient and graft survival by directing expanded criteria donor organs (ECD) to older recipients. Compared with organs from standard criteria donors, ECD kidneys are associated with impaired survival outcomes 8,9 but with increased life expectancy over dialysis in older recipients [10][11][12] ; however, less than two thirds of patients older than 65 y are willing to undergo transplantation with ECD kidneys, resulting in a high discard rate of this useful source. 13 Although many older individuals are suitable and should be offered a transplant, they are not routinely referred to KT, and their chance of actually receiving a transplant is low.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Current allocation policies attempt to match recipient and graft survival by directing expanded criteria donor organs (ECD) to older recipients. Compared with organs from standard criteria donors, ECD kidneys are associated with impaired survival outcomes 8,9 but with increased life expectancy over dialysis in older recipients [10][11][12] ; however, less than two thirds of patients older than 65 y are willing to undergo transplantation with ECD kidneys, resulting in a high discard rate of this useful source. 13 Although many older individuals are suitable and should be offered a transplant, they are not routinely referred to KT, and their chance of actually receiving a transplant is low.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding deceased donor graft quality, we only included transplants performed from donors with a low KDPI, as high KDPI correlates negatively with graft survival. [28][29][30] Furthermore, only cases with a CIT ≤18 h were chosen because longer times have a detrimental impact on graft outcomes. 31 KT performed with an HLA mismatch >4 was excluded because 5 and 6 donor-recipient HLA mismatch have a kidney graft failure hazard ratio ≥1.5.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Park et al . [ 32 ] examined the impact of KDRI on post-transplant clinical outcomes between elderly and young recipients, and revealed that the high KDRI-young recipients group has worse allograft outcome than the three other groups (i.e. low KDRI-young recipients, low KDRI-elderly recipients and high KDRI-elderly recipients).…”
Section: Discussionmentioning
confidence: 99%